Toll-like receptor 1 polymorphism is associated with impaired immune tolerance, dysregulated inflammatory responses to Borrelia burgdorferi, and heightened risk of post-infectious Lyme arthritis - Williams, Morgan A.; Hernandez, Sergio A.; Arvikar, Sheila L.; Sulka, Katherine B.; Strle, Franc; Wells, Christopher C.; Petnicki-Ocwieja, Tanja; Steere, Allen C.; Strle, Klemen (Frontiers in Immunology, 2025)
IntroductionClinical presentation of Lyme disease is largely due to host immune response to infection. Previously, we identified a variant (1805GG) in the TLR1 gene, a key immune sensor for Borrelia burgdorferi, which was associated with excessive inflammation and severe disease. Herein we examined the mechanism by which this variant leads to dysregulated immunity.MethodsWe found that patients with post-infectious Lyme arthritis, a condition characterized by marked persistent synovitis in joints, have a higher frequency of TLR1-1805GG compared to those whose arthritis resolves with antibiotics. To explore the possibility that this genotype-phenotype association was due to excessive inflammation, we then tested the functional impact of TLR1-1805GG on inflammatory responses and immune tolerance in PBMCs with or without this SNP and in THP-1 cell lines lacking TLR1.ResultsIn response to B. burgdorferi stimulation, PBMCs with TLR1-1805GG had greater transcriptional upregulation of 1200 immune-related genes and significantly higher cytokine levels in supernatants compared to cells without this variant. Moreover, repeat B. burgdorferi stimulation, which mimics tolerogenic conditions during the infection, failed to induce innate immune tolerance in PBMCs with TLR1-1805GG, or in THP-1 cells lacking TLR1, resulting in seemingly unabated immune activation consistent with marked inflammation in Lyme arthritis joints.ConclusionsThese results suggest that excessive inflammation in patients with TLR1-1805GG variant appears to be due to immune dysregulation and inability to induce immune tolerance. The findings help explain how early events during the infection may contribute to sustained immune activation after antibiotics and point to the role of TLR1 signaling in immune regulation.